Bioactivity Evaluation and Phytochemical Characterization of Euonymus alatus (Thunb.) Siebold Leaf Extract - Won-Joo Yoon; Hye-Ji Min; Hyun-Dong Cho; Hwi-Gon Kim; Wool-Lim Park; Du-Hyun Kim; Hirofumi Tachibana; Kwon-Il Seo (Biomedicines)
Background: Euonymus alatus (E. alatus) has traditionally been used for medicinal purposes, and its leaves are considered edible. While E. alatus is known for its diverse biological activities, the antioxidant, antidiabetic, and anticancer effects of its leaves extracted using different solvents have not been thoroughly investigated. Methods: This study examined the antioxidant, antidiabetic, anticancer, and life-prolonging effects of Euonymus alatus (E. alatus) leaf extract. Results: The phytochemical analysis showed that the ethanol extract contained the highest levels of polyphenols (347.2 mg/mL) and flavonoids (317.7 mg/mL) compared to the water and methanol extracts. In addition, specific phenolics, such as rutin, ellagic acid, and quercetin, were found in the ethanol extract. Antioxidant assays showed that the ethanol extract exhibited superior DPPH, ABTS radical, and H2O2-scavenging activities, as well as reducing power. In addition, the ethanol extract displayed strong α-glucosidase inhibitory activity in a dose-dependent manner. In cancer cell studies, the ethanol extract selectively inhibited the proliferation of MDA-MB-231 (breast) and LNCaP (prostate) cancer cells without affecting normal cells. Apoptosis induction was confirmed by nuclear condensation and increased caspase-3 activity. Furthermore, treatment with 30 mg/kg/day of the extract extended the lifespan of the tumor-bearing mice to 50 days, with no fatalities, indicating a dose-dependent protective effect. Conclusions: E. alatus leaf ethanol extract has potential as an antioxidant, antidiabetic, anticancer, and life-prolonging agent.